Seasonal patterns in extracellular ion concentrations and pH of the Arctic copepod Calanus glacialis. (4th September 2015) - Freese, Daniela; Niehoff, Barbara; Søreide, Janne E.; Sartoris, Franz Josef
Abstract: Arctic shelf zooplankton communities are dominated by the copepod Calanus glacialis . This species feeds in surface waters during spring and summer and accumulates large amounts of lipids. Autumn and winter are spent in dormancy in deeper waters. Lipids are believed to play a major role in regulating buoyancy, however, they cannot explain fine‐tuning of the depth distribution. To investigate whether ion exchange processes and acid‐base regulation support ontogenetic migration as suggested for Antarctic copepods, we sampled C. glacialis in monthly intervals for 1 yr in a high‐Arctic fjord and determined cation concentrations and the extracellular pH (pHe ) in its hemolymph. During the winter/spring transition, prior to the upward migration of the copepods, Li + ions were exchanged with cations (Na +, Mg 2+, and Ca 2+ ) leading to Li + concentrations of 197 mmol L −1 . This likely decreased the density and promoted upward migration in C. glacialis . Our data thus suggest that Li + has a biological function in this species. Ion and pHe regulation in the hemolymph were not directly correlated, but the pHe revealed a seasonal pattern and was low (5.5) in winter and high (7.9) in summer. Low pHe during overwintering might be related to metabolic depression and thus, support diapause.